Anti-CD 19 and anti-CD 20 CAR-modified T cells for B-cell malignancies: a systematic review and meta-analysis. (September 2017) - Riaz, Irbaz Bin; Zahid, Umar; Kamal, Muhammad Umar; Husnain, Muhammad; McBride, Ali; Hua, Anh; Hamadani, Auon Abbas; George, Laeth; Zeeshan, Ali; Sipra, Qurat-ul-Ain Riaz; Raina, Ammad; Rahman, Bushra; et al.
Chimeric antigen receptor modified T cells targeting CD19 and CD20 have shown activity in Phase I, II trials of patients with hematological malignancies. We conducted a systematic review and meta-analysis of all published clinical trials studying the role of efficacy as well as safety of CD-19 and CD-20 chimeric antigen receptor-T therapy for B-cell hematologic malignancies. A total of 16 studies with 195 patients were identified. The pooled analysis showed an overall response rate of 61% (118/195) with complete response of 42% (81/195) and partial response of 19% (37/195). Major adverse events were cytokine release syndrome 33%, neurotoxicity 33% and B-cell aplasia 54%. Collectively, the results indicate encouraging response in relapsed/refractory B lymphoma and leukemia, especially in acute lymphoblastic leukemia (ALL) patients.